2022
DOI: 10.3390/cells11071166
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Protein Translation and Carboxylic Acid Catabolic Processes in Diabetic Kidney Disease

Abstract: Diabetic kidney disease (DKD) remains the leading cause of end-stage kidney disease despite decades of study. Alterations in the glomerulus and kidney tubules both contribute to the pathogenesis of DKD although the majority of investigative efforts have focused on the glomerulus. We sought to examine the differential expression signature of human DKD in the glomerulus and proximal tubule and corroborate our findings in the db/db mouse model of diabetes. A transcriptogram network analysis of RNAseq data from la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The acetyl-CoA metabolite was downregulated in db/db mice, consistent with the differential expression of the genes Acoxl and Acacb . These findings suggest that PT alterations and carboxylic acid catabolism during protein translation are key features of human and mouse DKD ( Collins et al, 2022 ).…”
Section: Application Of Single-cell Transcriptomics In Diabetic Kidne...mentioning
confidence: 87%
See 1 more Smart Citation
“…The acetyl-CoA metabolite was downregulated in db/db mice, consistent with the differential expression of the genes Acoxl and Acacb . These findings suggest that PT alterations and carboxylic acid catabolism during protein translation are key features of human and mouse DKD ( Collins et al, 2022 ).…”
Section: Application Of Single-cell Transcriptomics In Diabetic Kidne...mentioning
confidence: 87%
“…A study on human and mouse DKD found carboxylic acid catabolic process, steroid hormone biosynthesis, glutathione metabolism, and biological oxidation were enriched in PT cells. Among these, the carboxylic acid catabolic process is the top pathway identified in mouse snRNA-seq and human datasets ( Collins et al, 2022 ). Spatially resolved metabolomics by mass spectrometry imaging revealed that increased glycolysis, mitochondrial dysfunction, AMPK inhibition, and lipid metabolism disorders occurred in a region-specific manner in the kidneys of rats with DKD ( Wang et al, 2021 ).…”
Section: Specific Cell Types and Associated Signaling Pathways For Dkdmentioning
confidence: 99%
“…60 This increase in mRNA translation could be caused by matrix accumulation and higher amounts of growth factors, both of which are prevalent in tubular injury and progressive DKD. 61 An imbalance brought about by an increase in protein synthesis and degradation can progress to ER stress, 60 which is one of the critical mechanisms in albumin-induced tubular injury. 62 Several limitations of this study should be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Translation pathways have been reported enriched in the proximal tubules of DKD kidney biopsies compared to controls. 60 This increase in mRNA translation could be caused by matrix accumulation and higher amounts of growth factors, both of which are prevalent in tubular injury and progressive DKD. 61 An imbalance brought about by an increase in protein synthesis and degradation can progress to ER stress, 60 which is one of the critical mechanisms in albumin-induced tubular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is a result of a complex interaction between metabolic processes, is a result of long-term tubular ( 5 , 6 ) and glomerular damage, and is an important cause of renal failure ( 7 ) and inflammatory and hemodynamic change ( 3 ). Its key risk factor is insulin resistance.…”
Section: Introductionmentioning
confidence: 99%